THEORETICAL AND CONCEPTUAL FRAMEWORKS: AN INVESTIGATION ON THE HURDLES LEARNERS WITH VISUAL IMPAIRMENT FACE ACADEMICALLY DUE TO THE INTRODUCTION OF INCLUSIVE EDUCATION IN TWO SELECTED SECONDARY SCHOOLS IN ITEZHI-TEZHI DISTRICT OF ZAMBIA - Nthama, Kapembwa; Annie, Penda (International Journal of Research -GRANTHAALAYAH, 2019)
This manuscript is an extract of a theoretical framework and conceptual framework from a Master’s an on-going study on the hurdles learners with visual impairment face academically due to the introduction of inclusive education in two selected secondary schools in Itezhi-tezhi District of Zambia. The work is an attempt to identify the hardles affecting learners with visual impairment in Zambia. Among the factors that can affect these learners are such as attention, materials, financial support, trained teachers, and attitude. It is argued that if these factors are identified and addressed learners with visual impairment can benefit a lot from education under education system.